Empowerment of KUBE Based on Regions in the South Coastal Area of Pelabuhan Ratu Sukabumi - Kantirina Rachaju; Cepta Hery (SEAN Institute, 2025)
Empowerment of regional-based Joint Business Groups (KUBE) in the southern coastal area of Pelabuhan Ratu, Sukabumi, is a strategy to improve community welfare through strengthening community-based economics. This study aims to analyze the effectiveness of KUBE empowerment in increasing the economic and social capacity of coastal communities, as well as identifying supporting and inhibiting factors in its implementation. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results of the study show that regional-based KUBE empowerment in Palabuhanratu has a positive impact on improving the welfare of coastal communities. This program has succeeded in increasing fishermen's productivity through modernization of fishing gear and more efficient fisheries cultivation. In addition, business diversification such as seafood processing and marine tourism development has opened up new economic opportunities for local communities. Support in the form of business management training, access to capital, and digital marketing has also been proven to increase the competitiveness of KUBE products in the wider market. With the synergy between the community, government, and private sector, KUBE can develop independently and sustainably, while supporting regional economic growth based on local resources.